Exploring student perspectives in amplifying students' speaking skills on English for hospitality internship - Ananta, Benny Dele Bintang; Sholahuddin, Muhammad Firza Thoriq; Waloyo, Alimin Adi (English Learning Innovation, 2024)
This research focuses on the experiences of hospitality internships in amplifying speaking skills. In particular, the objective of this research is to examine the students’ perspectives in the hospitality program on enhancing speaking skills as well as the challenges they face and their solutions to these challenges. Qualitative research methods, including questionnaires and observations, were used to gather data from students in the English Language Education Department at the University of Muhammadiyah Malang, Indonesia. There were 28 students enrolled in COE English for Hospitality Program, who participated in the study. The results showed that students' opinions about their experiences with speaking education during their hospitality internships varied. Additionally, challenges in hospitality internships encompass three main areas: delivery, language, and interaction. Some strategies were also provided to assist in overcoming the difficulties identified. It is accordingly advocated that teachers and students need to prepare better in terms of delivery, language, and interaction. hospitality internships can be implemented in the class and Internship programs.